Evaluation of biological agents with cover crops for sustainable agriculture: Literature review - Confesora Pinales Ramírez; Emmanuel Torrez Quezada; Willy Maurer; Omar Paíno Perdomo (Annals of Environmental Science and Toxicology - Peertechz Publications, 2023)
Cover crops combined with biological agents constitute a promising alternative to improve soil health and contribute to the environmental sustainability of agricultural systems, for which a search has been carried out whose objective was to carry out a critical analysis of the existing literature on agents, bioremediation with cover crops for sustainable agriculture. In exploratory non-experimental research, a content analysis of scientific articles identified in the Web of Science databases and through Google Scholar was carried out. It was investigated starting in 2012 for a period of 10 years regarding the type of documents, field of thematic area, number of publications per year, and leading countries. Of the types of documents analyzed, 58 works corresponding to scientific articles were selected, of which, most of them located in the area of microbiology, whose set of results shows that the highest number of publications was reached in 2021, with 31 %. For the countries that publish the most on the subject, the People's Republic of China is leading with 57%. These numbers plot the publication outlook for the topic based on the selected keywords; and reflect a continuous increase in published works on the implementation of this production technique to provide solutions based on sustainability, safety, and food security. However, studies are required that make it possible to strengthen management systems in order to increase their reliability and performance in producers.